A note on communicating environmental change for non-market valuation. (January 2017) - Fu, Baihua; Dyer, Fiona; Kravchenko, Alexey; Dyack, Brenda; Merritt, Wendy; Scarpa, Riccardo
Highlights: We explore options for formulating environmental change for valuation studies. All formulations have limitations depending on context. The choice of formulation reflects philosophical stance. The assumptions associated with the formulation must be clearly defined. A graphical method is proposed to reduce limitations of formulations. Abstract: Communicating change in environmental condition is a critical component of non-market valuation studies. However, the underlying assumptions and implications associated with alternative ways of expressing change in environmental condition for surveys are rarely discussed in the literature. Our review found no cases where alternative formulations were both discussed and tested. In this note we report on our multi-disciplinary analysis of how best to express such change. We interrogate the meaning of, and inferences from, four formulations for quantitative expressions, or metrics, of environmental indicators that are used in the field of ecology and we then evaluate their usefulness in non-market valuation. The assumptions and limitations of each formulation are discussed using seven hypothetical cases of change in environmental condition. We show that formulations for expressing change can be grouped based on two inherent philosophies potentially held by people when they consider their preferences for environmental changes: 'more is better philosophy' and 'restoration philosophy'. We contend that, without careful consideration of which philosophy people may apply, it is possible to inadvertently bias respondent choices when a particular formulation is used in a valuation study. If this happens, resulting value estimates will be a poor reflection of what researchers seek. An alternative approach that does not presuppose a philosophy but instead helps reveal a respondent's philosophy, is proposed.